Sintesis dan karakterisasi komposit polipropilena/silika berbasis abu ampas tebu - Idra Herlina; Yulistia Anggraini; Edwin Rizki Safitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
Polypropylene/sugarcane bagasse silica (PP/SiO2) composites have been synthesized. The sol gel method with 1 M NaOH was used to synthesize silica from bagasse ash. The results showed that the silica yield was 52.8%. The resulting silica was blended with polypropylene with a mass ratio variation of 1:5, 1:10, 1:15, 1:20, and 1:25 to obtain PP/SiO2 composites. Composites in variations of 1:5 and 1:10 produce fragile plastic, whereas composites in variations 1:15, 1:20, and 1:25 produce strong and homogeneous plastic. The water resistance test showed that PP/SiO2 with variations of 1:15, 1:20,and 1:25 had good water resistance (> 94%), whereas variations of 1:5 and 1:10, the resistance to water dropped to 80-87%. FT-IR was used to characterize polypropylene, silica synthesized from bagasse ash, and PP/SiO2 composites (1:25) to observe functional group changes. FT-IR analysis showed that silica was successfully synthesized from bagasse ash. This is indicated by a band that widened at a wavenumber of 3400-3600 cm-1, which is characteristic of the O-H strain on water. This band is confirmed by a band with a wavenumber of 1660 cm-1 which is a bend in the O-H in a water molecule. Other silica characteristics can be seen in bands with wavenumbers of 1075 cm-1 and 950 cm-1, which are strains of Si-O, and bands with a wavenumber of 460 cm-1, which is a bend of Si-O. The spectra of polypropylene and PP/SiO2 were also similar. The similarity between the polypropylene and PP/SiO2 spectra indicates that SiO2 spreads homogeneously in polypropylene.